Strategi Pembelajaran Pendidikan Agama Islam - Nurdin; Zubairi, Zubairi (Tarqiyatuna: Jurnal Pendidikan Agama Islam dan Madrasah Ibtidaiyah, 2023)
Strategies in learning Islamic religious education must be carried out by a teacher, considering that the teacher is an important and main factor, because the teacher is the person who is responsible for the cognitive, psychomotor and affective development of students, especially in schools. Therefore, the purpose of this study was to find out the learning strategies by Islamic religious education teachers. The method used is library research and uses descriptive narrative analysis. The results of the study show that in order to achieve this goal, the maturity of students must be taught how to become fully human and know their duties as human beings. In a special sense, it can be said that every teacher has the responsibility to bring students to maturity or a certain level of maturity. Within this framework the teacher is not merely an "educator" who transfers knowledge, but also a "educator" who transfers values and at the same time as a "guide" who gives direction and guides students in learning to achieve learning goals.